Insurrection : a teacher revolution in defense of children - Reeves, Keith David (Emerald Publishing Limited : Information Age Publishing Inc., 2016)
Enough. Private interests, politicians, reformers, and pundits have had their chance, and enough is enough. Teachers have been pushed around and pushed to the edge, and the time for tolerating the failed system of our public education policies is over. It's time to drag the standardized testing commercial complex out of our schools, kicking and screaming if need be, and take back our schools for our kids. The revolution has already begun.We must understand the etiology of the American public school's seeming inability to meaningfully and holistically teach every child if we are to have any hope of changing that school for the better. We must wrestle with the philosophical, sociological, and psychological roots of our misperception and mistreatment of children in order to change the way we understand our students. We must also understand the history of 'reform' in American education in order to avoid repeating failed experiments. Once we do this, we can dismantle the traditional structures of the American Public School deliberately and thoughtfully, and capitalize upon the intense zeitgeist of the movement against corporatized standardized multiple choice testing, in order to truly revolutionize our schools.Over five sequential sections, 'Insurrection' addresses educational philosophy, the system of schools, the social issue of misunderstanding children, replacement structures for those that are incompatible with understandings corrected in the first three sections, and a possible manner in which current school employees can lend their efforts to the revolution called for by Sir Ken Robinson in his 2010 TED Talk, which served as the impetus for the work.